Adjectival Agreement in Middle and Early Modern Welsh Native and Translated Prose. (1st January 2020) - Meelen, Marieke; Nurmio, Silva
This paper investigates adjectival agreement in a group of Middle Welsh native prose texts and a sample of translations from around the end of the Middle Welsh period and the beginning of the Early Modern period. It presents a new methodology, employing tagged historical corpora allowing for consistent linguistic comparison. The adjectival agreement case study tests a hypothesis regarding position and function of adjectives in Middle Welsh, as well as specific semantic groups of adjectives, such as colours or related modifiers. The systematic analysis using an annotated corpus reveals that there are interesting differences between native and translated texts, as well as between individual texts. However, zooming in on our adjectival agreement case study, we conclude that these differences do not correspond to many of our hypotheses or assumptions about how certain texts group together. In particular, no clear split into native and translated texts emerged between the texts in our corpus. This paper thus shows interesting results for both (historical) linguists, especially those working on agreement, and scholars of medieval Celtic philology and translation texts.